And Yet It Moves: A High‐Temperature Neutron Diffraction Study of Ion Diffusion in the Inverse Perovskites BaLiX3 (X = F, H, D). Issue 48 (20th December 2019) - Wiedemann, Dennis; Heppke, Eva Maria; Franz, Alexandra
Abstract : Despite the interest in (anti‐)perovskites and diverse hydrides as hydride conductors and all‐solid‐state battery materials, little experimental evidence on anion diffusion in these compounds is available. Herein, we use neutron diffraction at high temperatures to discover pathways and estimate activation barriers of anion migration in mechanosynthesized powders of BaLiF3, BaLiH3, and BaLiD3 . We critically assess the limitations of both current methods for deriving effective one‐particle potentials (i.e., via modelling of the probability‐density function and via maximum‐entropy reconstruction of the scatterer density). The suggested migration pathways run roughly along the edges of the Li X 6 octahedra with activation energies of 0.45(3), ca. 0.41, and less than 1.44(3) eV in BaLiD3, BaLiH3, and BaLiF3, respectively. Not only is this the first determination of diffusion barriers in these hydrides but also the second study providing any comparative data on the two methods of derivation. Abstract : In powders of BaLi X 3 ( X = F, H, D), thermally activated anion diffusion occurs roughly along edges of the Li X 6 coordination octahedra with migration barriers of 0.4–0.5 eV for the hydrides. Each of the two established methods for their derivation ( via PDF modelling and MEM reconstruction) chips in with its own set of limitations to consider.